A Rare Anomaly of the Long Head of the Biceps Brachii Muscle - Kumar, S; Baidya, R; Baral, P (Journal of Gandaki Medical College-Nepal, 2018)
Introduction: Biceps brachii is a muscle of arm which brings about supination when fore-arm is flexed and flexion of elbow joint. Proximally it is attached with two heads: long and short heads. Case report: The absence of long head of biceps brachii muscle is very rare anomaly. It may be unilateral or bilateral with or without other congenital anomalies. The exact prevalence of this anomaly is unknown. This anomaly has been reported to occur as the result of an insult to the fetus during the sixth or seventh week of gestation, at which time the long head of the biceps tendon is developing. J-GMC-N | Volume 11 | Issue 01 | January-June 2018, Page:56-57